An online intervention to improve the health and well-being of informal caregivers of individuals with Alzheimer's disease: A pilot study - Yujun Liu; M. Courtney Hughes; Abby Baumbach; Lily Derain (Elsevier, 2023)
Objective: Describe an intervention to improve the health and well-being of informal caregivers of individuals with Alzheimer's disease (AD) and present pilot program findings. Methods: Participants (N = 31, mean age = 45.7) were randomly assigned to one of two conditions: an online synchronous didactic lesson and peer support session series or an asynchronous didactic only session series. Outcome variables included physical health, nutrition intake, and stress. One-way ANOVA was conducted to examine the effects of the intervention. The least significant difference (LSD) post hoc test was used to analyze the difference pattern between means. Results: Participants in both conditions reported healthier dietary behavior and lower level of stress from pre-intervention to the post-intervention. These effects were not maintained at one-month follow up. Conclusion: An online educational intervention may improve the health and well-being of informal caregivers of people with AD. Further research is necessary to determine which specific intervention components to include and what strategies may help participants maintain improved health behaviors. Innovation: This program focused on the health and well-being of informal caregivers of individuals with AD rather than on emphasizing how caregivers can perform their caregiving duties better. The intervention was provided in an underserved lower-income, rural area.